Gaining from scientific knowledge: the role of knowledge accumulation and knowledge combination - Kuo, Chia‐I; Wu, Chia‐Hung; Lin, Bou‐Wen (R & D management, 2019)
This study investigates the performance effect of scientific knowledge in the context of highly science‐dependent industry. Given the popularity of sourcing scientific knowledge from science community, the purpose of this study is to investigate which firms gain greater benefits from scientific knowledge. From the perspective of absorptive capacity and combinative capability, we argue that both knowledge accumulation and knowledge combination moderate a firm's ability to capture value from scientific knowledge. Empirical data come from paper and patent citations and financial information in biotechnology and pharmaceutical firms. Results show that scientific knowledge alone has a positive effect on firms' financial performance. A firm's tendency to combination familiar and older technological knowledge amplifies the positive effect of scientific knowledge. However, knowledge accumulation, including R&D investment and patent stock, does not boost the positive effect.